LAKTASUIT : KOSTUM LAKTASI UNTUK IBU AKTIF - Afifah, Yasmin Noor; Amalina, Fadiah Nur; Indriasari, Amelia Devy; Hidayatun, Putri Istiqomah Rizki; Kusumastuti, Jayanti Ayu (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Breastfeeding is important for childrenâs growth and development also Motherâs health. Based on SDKI (Indonesia Demograpic and Health Survey) 2012, mothers who do exclusive breastfeeding is increasing. We see this data as a chance for entrepreneurship. Then we have a n idea to make an innovation breastfeeding suit. An easy and comfort suit for breastfeeding named Laktasuit. Laktasuit will make a new paradigm about easy breastfeeding for all active mothers in Indonesia. The process of production is in cooperation with convections. We promoted our products by online and offline medias and distributed as wide as possible. Laktasuit has been distributed to many cities either in Java or other islands. We concluded that Laktasuit is promising with a great prospect and wide potential market. Itâs also potential product for campaigning exclusive breastfeeding.Â Keywords: laktasuit, active mother, breastfeeding, fashion